A pH-responsive wormlike micellar system of a noncovalent interaction-based surfactant with a tunable molecular structure. Issue 6 (18th January 2017) - Kang, Wanli; Wang, Pengxiang; Fan, Haiming; Yang, Hongbin; Dai, Caili; Yin, Xia; Zhao, Yilu; Guo, Shujun
Abstract : A pH-responsive wormlike micellar system based on the molecular structure variation of a noncovalent constructed surfactant has been developed. Abstract : Responsive wormlike micelles are very useful in a number of applications, whereas it is still challenging to create dramatic viscosity changes in wormlike micellar systems. Here we developed a pH-responsive wormlike micellar system based on a noncovalent constructed surfactant, which is formed by the complexation of N -erucamidopropyl- N, N -dimethylamine (UC22 AMPM) and citric acid at the molar ratio of 3 : 1 (EACA). The phase behavior, aggregate microstructure and viscoelasticity of EACA solutions were investigated by macroscopic appearance observation, rheological and cryo-TEM measurements. It was found that the phase behavior of EACA solutions undergoes transition from transparent viscoelastic fluids to opalescent solutions and then phase separation with white floaters upon increasing the pH. Upon increasing the pH from 2.03 to 6.17, the viscosity of wormlike micelles in the transparent solutions continuously increased and reached ∼683 000 mPa s at pH 6.17. As the pH was adjusted to 7.31, the opalescent solution shows a water-like flowing behaviour and the η 0 rapidly declines to ∼1 mPa s. Thus, dramatic viscosity changes of about 6 magnitudes can be triggered by varying the pH values without any deterioration of the EACA system. This drastic variation in rheological behavior is attributed to the pH dependent interaction between UC22 AMPM and citric acid. Furthermore, the dependence on concentration and temperature of the rheological behavior of EACA solutions was also studied to assist in obtaining the desired pH-responsive viscosity changes.